Experimental evaluation of effectiveness of lip seal of cylinder-piston group of long-stroke compressor stage - S. S. Busarov; V. L. Yusha; R. E. Kobylskiy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In slow-moving compressor stages the piston-cylinder seal is one of the most critical components affecting the tightness of the working chamber. In the present work, conditional clearances in the lip seal of low-speed compressor stages are determined by the method of static blowing. A comparative assessment of the leak-tightness of the piston-cylinder seal with a different number of cuffs and different wall temperatures is carried out